Juremologia: uma busca etnográfica para sistematização de princípios da cosmovisão da Jurema Sagrada. - L'odò, Alexandre L'omi (2017)
This research aimed to map the discourse coming from several religious communities of Jurema Sagrada in Recife and in its Metropolitan Region, which defend that "Jurema is the primate religion of Brazil" and the existence of a religious system of its own, which is its worldview, to which I have opted to call a juremological system. The methodology we used was the technique of dense ethnography (GEERTZ: 1978), the bibliographical and paleographic survey (to make a large survey of the existing texts, to systematize its historical and anthropological debate) and participatory field research, in a perspective, based on the qualified speeches of the juremeiros (male priests) and juremeiras (female priests) of tradition, to systematize this cosmos, which until then, had not been described and debated in the existing bibliography. With this, we seek to make an assertion by taking the Sacred Jurema as a religious and social phenomenon in the field of the sciences of religion.